The Role of Village Leaders and the Allocation of Government Grants on the South Korean Rural Development - Yang, Hyunjoo; Kim, Sunjin; Kim, Tae Jong (KDI School of Public Policy and Management, 2020)
This report contains two chapters. The first chapter, “The role of village leaders on the production of public goods: Evidence from South Korea,” considers the role of village leaders in the Korean rural development in the early 1970s. Under the New Village Movement (Saemaul Undong), the role of village leaders was considered as one of the most important factors for the success of the Movement. However, there has been few empirical research documenting the relationship between the leaders and their roles on the improvement of village through the Movement. Using novel data on the village leaders and Saemaul classifications, we show that villages with village leaders who had relatively better educational attainment tend to improve their village public goods in two years. High human capital of both male and female village leaders mattered for the improvement of public goods. The second chapter, “The Allocation of Government Grants in the Community Development Program,” shows that the government resource allocation in the 1970s was not matched with outcomes of Saemaul projects. Despite government documents and anecdotal evidences from Saemaul practitioners that the government selectively provided grants only to the better-performing villages in Saemaul projects, we find that there is no empirical evidence that verifies the performance-based support system.